Expressive-Musical Playfulness: reflections on childhood development - Morgado, Elsa Maria Gabriel (2023)
Sounds and music are present in life from birth. In schools, early childhood music education is recognized as an important curricular contribution to the expansion of cultural habits and achievements contributing to sociability since music is extremely collaborative in this regard. In addition, it stimulates memorization, an important skill for future learning. In this paper we present a reflection about the manifestation of children's talent, educational procedures and their generous effects on the brain, support for the mind, which will be indispensable for the personal and intellectual evolution of the learner.  We emphasize that playfulness is an important factor in learning because play is natural to children. The present study allows us to appreciate the dimension of specific activities from the musical initiation, verifying how and why they should be applied as a potential conductor for personal and cognitive evolution in early childhood education. In this research, we intend to make a theoretical and empirical approach to the importance of playfulness in learning the art of music.